Synthesis and Characterization of Cyclopropaosmanaphthalenes Containing a Fused σ‐Aromatic Metallacyclopropene Unit. (21st May 2019) - Chu, Zhenwei; He, Guomei; Cheng, Xiaoli; Deng, Zhirong; Chen, Jiangxi
Abstract: Metalla‐aromatics are important complexes that show unique properties owing to their highly conjugated systems, which show Hückel or Möbius aromaticity. Recently, several metalla‐aromatics showing spiro‐aromaticity or σ‐aromaticity have been reported. Herein, we report the isolation of the first cyclopropametallanaphthalenes, in which the metallacyclopropene ring shows σ‐aromaticity and weak hyperconjugative aromaticity. The reaction of OsCl2 (PPh3 )3 with o ‐ethynylphenyl alkynes in the presence of PPh3 followed by protonation with HCl yielded the first cyclopropametallanaphthalenes. The reaction mechanism and the aromaticity were also investigated by density functional theory studies. Abstract : Eingeschraubtes Osmium : Das erste Cyclopropametallanaphthalen wurde durch die Reaktion von OsCl2 (PPh3 )3 mit einem o ‐Ethinylphenylalkin in Anwesenheit von PPh3 gefolgt von einer Protonierung mit HCl hergestellt. Die Aromatizität des Moleküls wurde mit DFT‐Rechnungen untersucht, die σ‐Aromatizität und schwache hyperkonjugative Aromatizität in der ungesättigten Metallacyclopropen‐Untereinheit bestätigten.